If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 5 + 3x Reorder the terms: -2 + 4x = 5 + 3x Solving -2 + 4x = 5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 4x + -3x = 5 + 3x + -3x Combine like terms: 4x + -3x = 1x -2 + 1x = 5 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 1x = 5 + 0 -2 + 1x = 5 Add '2' to each side of the equation. -2 + 2 + 1x = 5 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = 5 + 2 1x = 5 + 2 Combine like terms: 5 + 2 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| 7/10+1/5a=1/2a | | 21-11x=17-33 | | Y=-15x+20 | | 5y-2=64-6y | | n/5=6-n/10 | | h=-16t+38.4-t+3.5 | | 8x-(2x-5)=29 | | 3x-5+15= | | 7x+282=9y+278 | | -(w+3)=-3w+16 | | 136-5= | | (0.85x)-10= | | 10v-4v+34=100 | | p-8=2 | | 9z+6-2z=9+6z+3 | | 3a+2+(5a+1)= | | 30x^2+60x+30=0 | | 16-q=7 | | 8x=4x-22 | | 4+m=19 | | j-1=9 | | 5x+5=3(x+3) | | 9n+6=42 | | p(x)=x^3+3x^2-16x+12 | | (12d-8)=8d-5 | | b-7=4 | | -5(x+4)+6x=7x+8 | | 112.2-3.8x=8.2x+36.6 | | 4x+30=22 | | log(6x)-log(3)= | | .45=logx | | 14a-a=6 |